2004
DOI: 10.1111/j.0269-8463.2004.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of tiller recruitment in bunchgrasses: uniting physiology and ecology

Abstract: Summary 1.Bunchgrasses are clonal plants whose dominance of moist grasslands worldwide is maintained largely through tiller recruitment. Tiller recruitment in clonal plants is a subset of the problem of lateral bud outgrowth in higher plants. This paper proposes that three currently competing hypotheses of lateral bud outgrowth -apical dominance; the nutrition hypothesis; and photosensitivity to the red : far-red light ratio -all operate in a manner dependent on environment and plant form. 2. The evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 67 publications
4
49
1
1
Order By: Relevance
“…The light cues that signal dormant buds to emerge as shoots may be blocked or altered by the detritus layer in unburned prairie. Based on studies of C 3 grasses, Tomlinson and O'Connor (2004) proposed that an interaction of light (red/far-red light ratio) and nitrogen regulate bud outgrowth and shoot emergence. Williamson et al (2012) tested the Tomlinson and O'Connor model and found that while C 3 grasses responded as predicted to light and nitrogen availability, with increased tillering under higher light and nitrogen levels, C 4 grasses did not.…”
Section: Sensitivity Of Bud Bank Density and Demography To Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…The light cues that signal dormant buds to emerge as shoots may be blocked or altered by the detritus layer in unburned prairie. Based on studies of C 3 grasses, Tomlinson and O'Connor (2004) proposed that an interaction of light (red/far-red light ratio) and nitrogen regulate bud outgrowth and shoot emergence. Williamson et al (2012) tested the Tomlinson and O'Connor model and found that while C 3 grasses responded as predicted to light and nitrogen availability, with increased tillering under higher light and nitrogen levels, C 4 grasses did not.…”
Section: Sensitivity Of Bud Bank Density and Demography To Droughtmentioning
confidence: 99%
“…Williamson et al (2012) tested the Tomlinson and O'Connor model and found that while C 3 grasses responded as predicted to light and nitrogen availability, with increased tillering under higher light and nitrogen levels, C 4 grasses did not. The primary controls over bud transition to shoots in tallgrass prairie are most likely temperature (Knapp and Hulbert 1986), light (Deregibus et al 1985, Tomlinson and O'Connor 2004, Williamson et al 2012, and nitrogen (Bonser and Aarssen 2003, Tomlinson and O'Connor 2004, Williamson et al 2012.…”
Section: Sensitivity Of Bud Bank Density and Demography To Droughtmentioning
confidence: 99%
“…Bunchgrasses reproduce in two distinct manners (1) through seedling recruitment and (2) production of lateral tiller (Tomlinson and O'Connor 2004). For our study we quantified reproduction based on measures of reproductive effort and allocation related to seedling recruitment by measuring (1) flowering vs. nonflowering individuals, (2) the number of flowering tillers per individual, (3) the total number of spikelets, and (4) allocation of spikelets per flowering tiller.…”
Section: Plant Reproductive Effort Growth and Biomass Allocationmentioning
confidence: 99%
“…This also indicates that, among the four NWSGs, SG establishment was less susceptible to weed competition, and therefore, under comparable growing conditions, the productivity of fall-seeded new stands of similar varieties may benefit more from careful early defoliation management that promotes tillering than it might with intensive weed control alone. Defoliation usually favors the growth of auxiliary tillers through improved light environment (Assuero & Tognetti, 2010) and the removal of the reproductive tillers'' apical dominance (Richards, et al, 1988;Briske and Richards, 1995;Tomlinson and O'connor, 2004). However, when deciding on appropriate defoliation strategies, species differences in response to defoliation as in the case of SG in the current study should be taken into consideration.…”
Section: Effects Of Species On Forage Yieldmentioning
confidence: 92%